2016
DOI: 10.1177/1062860615583671
|View full text |Cite
|
Sign up to set email alerts
|

TeamSTEPPS Improves Operating Room Efficiency and Patient Safety

Abstract: The objective was to evaluate the effect of TeamSTEPPS on operating room efficiency and patient safety. TeamSTEPPS consisted of briefings attended by all health care personnel assigned to the specific operating room to discuss issues unique to each case scheduled for that day. The operative times, on-time start rates, and turnover times of all cases performed by the urology service during the initial year with TeamSTEPPS were compared to the prior year. Patient safety issues identified during postoperative bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 18 publications
2
59
1
Order By: Relevance
“…It is easier for experienced nurses to anticipate needs and act efficiently compared with those who have less experience (Lingard et al, ), which increases the need for good team skills in the OR team. Weld et al () found that team training was associated with shorter operating times and an improvement of on‐time starts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is easier for experienced nurses to anticipate needs and act efficiently compared with those who have less experience (Lingard et al, ), which increases the need for good team skills in the OR team. Weld et al () found that team training was associated with shorter operating times and an improvement of on‐time starts.…”
Section: Discussionmentioning
confidence: 99%
“…All inter‐professional team members must be included in teaching, simulation and implementation of tools and strategies (Baker, Salas, Battles, & King, ). Research has shown that surgery‐related morbidity, mortality and the number of patient safety‐related intraoperative events were reduced significantly after team training (Forse, Bramble, & McQuillan, ; Gillespie et al, ; Johnson & Kimsey, ; Neily et al, ; Weld et al, ; Weller & Boyd, ). At the same time, OR efficiency increased and there were fewer delays (Shams et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although published research on team training in ambulatory care is extremely limited, our findings align with similar studies conducted in hospitals. Research involving implementation of TeamSTEPPS programs in acute care settings demonstrates improvements in observed team behaviors, 12,15,[19][20][21] staff perceptions of teamwork 15 and safety culture, 11,12,16,19,20,32 and patient satisfaction. 19,20 Recent literature reviews 2,7,10 and a meta-analysis 6 bolster the evidence that hospital-based team training interventions lead to improvements, not only in team outcomes but in clinical processes (eg, lengths of stay, procedure start times, and procedure duration) and patient outcomes (eg, adverse events, mortality) as well.…”
Section: Discussionmentioning
confidence: 99%
“…Medical team training has focused on hospital‐based acute care, with evidence supporting improvements in team attitudes, behaviors, and culture; clinical process measures; and patient outcomes . However, most patient care occurs in ambulatory facilities .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation